2022
DOI: 10.1530/eo-21-0033
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumors and the risk of other malignancies: is the relationship coincidental or causal?

Abstract: Pituitary adenomas are benign neoplasms of the pituitary. The most prevalent are prolactinomas and nonfunctioning pituitary adenomas, followed by growth hormone- and ACTH-secreting adenomas. Most pituitary adenomas seem to be sporadic and their persistent growth is very atypical. No molecular markers predict their behavior. The occurrence of pituitary adenomas and malignancies in the same patient can be either pure coincidence or caused by shared underlying genetic susceptibility involved in tumorigenesis. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…The association between NFPA and an increased risk of malignancy remains controversial [ 19 ]; thus, the co-occurrence of NFPA and HCC in our patient may be coincidental. Intriguingly, the oncogene pituitary tumor-transforming gene 1 (PTTG1), first identified in pituitary tumors in rats [ 20 ], is expressed in nearly 90% of NFPA cases [ 21 ].…”
Section: Discussionmentioning
confidence: 89%
“…The association between NFPA and an increased risk of malignancy remains controversial [ 19 ]; thus, the co-occurrence of NFPA and HCC in our patient may be coincidental. Intriguingly, the oncogene pituitary tumor-transforming gene 1 (PTTG1), first identified in pituitary tumors in rats [ 20 ], is expressed in nearly 90% of NFPA cases [ 21 ].…”
Section: Discussionmentioning
confidence: 89%
“…In the view of clinically and histologically excluded acromegaly, her mildly elevated IGF-1 (unaffected by treatment), could not be attributed to multiple myeloma as its source, but may have played a role in disease occurrence or progression. Populationwide studies associated a high normal IGF-1 with increased risk of various malignancies, including breast, prostate, lung and colorectal cancer [50]. In previous studies, elevated IGF-1 was not confirmed in multiple myeloma (MM) patients, but higher serum IGF-1 level was associated with worse prognosis of the disease [51].…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary adenomas are tumors, generally benign, of the pituitary gland. Recently, it has been hypothesized that heavy metals can also increase the risk of the onset of pituitary adenomas [75]. It is probable that, on the basis of this, there is a possible interaction between the AIP (Aryl hydrocarbon receptor-interacting protein)-AhR pathway and heavy metals.…”
Section: Heavy Metals and Other Brain Tumorsmentioning
confidence: 99%